Zatoichi the Fugitive Based on a Short Story by Kan Shimozawa - Tanaka, Tokuzô; Makiura, Chishi; Katsu, Shintaro; Takada, Miwa; Banri, Masayo (Zatoichi: The Blind Swordsman Collection, 2019)
Zatoichi triumphs at a village wrestling match, much to the chagrin of his yakuza opponents. The defeated gang members pay a hotheaded ronin to take out the masseur; unbeknownst to them, the hired assassin is married to a former flame of Zatoichi's, further complicating matters. [www.criterion.com]